Sistem Informasi Pengelolaan Tugas Akhir Menggunakan Metode User-Centered Design - Finsa Nurpandi; Anita Ilmaniati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
This research aims to develop a thesis management information system at the Faculty of Engineering, Suryakancana University. Based on the results of the analysis, the system built to solve problems regarding data management that is not centralized, there are still processes that are not optimal, and document search is still difficult. Processes that are managed in this system include data management for student thesis, scheduling, registration, and assessment. The research was conducted based on the Design Science Research Methodology information system guide which has stages of problem identification, setting goals, design and development, demonstration, evaluation, and communication. The system was developed using the Laravel framework that applies the Model View Controller (MVC) concept and uses the PHP programming language, and uses the MySQL database. System development uses a User-Centered Design approach, where development only focuses on the user so that it does not change the work flow, and work procedures that apply at the Faculty of Engineering, Suryakancana University.